Memory Awareness (Kesadaran Memori) pada Anak - Nur Fatwikiningsih (Journal An-Nafs: Kajian Penelitian Psikologi, 2017)
Memory awareness part of metacognitive. Children are able to monitoring their performance memory (metacognitive monitoring). The research with participant observation in children aged 4-11 years aims to examine accuracy memory awareness and children's understanding of their memory processes. The results of the observation indicate (t = - 4.239, p = 0.001) was a significant increase between the number of pictures can be succesfully remembered (predictions of confidence judgments) and actual performance. Young children were optimistic about their abilities to remember than the age above.